The Use of SO2 to Bind Acetaldehyde in Wine: Sensory Implications - Coetzee, C.; Buica, A.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2018)
It is thought that the formation of hydroxysulphonate when sulphur dioxide is added to wine containing free acetaldehyde negates the sensory impact of the latter compound, but little research has been done on this. Descriptive analyses were employed using a trained sensory panel to assess the sensory effect of sulphur dioxide and acetaldehyde as single compounds and in combination in model wine. The addition of acetaldehyde or sulphur dioxide as singular compounds led to large increase in especially the green apple or sulphur descriptors respectively. When these two compounds were added in equimolar concentrations, the green apple description decreased drastically; however, a prominent sulphur description was still noted. It thus seems that hydroxysulphonate also has a sulphur-like aroma. The hydroxysulphonate did not influence the perception of a prominent ester, isoamyl acetate, in model wine. A low pH influences the perception of sulphur when sulphur dioxide is present on its own, but this is not the case with hydroxysulphonate. The implications of these results for wine production are discussed further.